Pelatihan Pemanfaatan Canva bagi Guru TK dalam Pengembangan Media Pembelajaran di TK Rabiatul Aulad - Hilyatul Mustafidah; Khairunnas; Syahrul Alamsyah; Retno Ningsih (SEWAGATI: Jurnal Pengabdian kepada Masyarakat, 2026)
Limited teacher digital skills meant that fine-motor learning media at Rabiatul Aulad Kindergarten largely relied on worksheets from books and the internet that were not always aligned with children's needs. This community service program aimed to improve teachers' ability to design fine-motor learning media using Canva. The program included needs identification, material delivery, demonstrations, guided practice, and evaluation through observation and a product rubric. Participants practiced developing coloring, line-tracing, picture-matching, pasting, cutting, and bead-pattern cards with difficulty levels adjusted to children's ages. After the training, participants could use basic Canva features, write instructions, arrange visual elements, and produce print-ready media. Several participants also applied their design skills to business promotional content. The findings indicate a descriptive change in participants' abilities, but no quantitative improvement can be claimed because structured pre- and post-tests were unavailable. Mentoring, a shared design library, quantitative evaluation, and classroom testing are recommended to sustain the program.